2002
DOI: 10.1016/s0048-7333(01)00154-8
|View full text |Cite
|
Sign up to set email alerts
|

Technological trajectories as moderators of firm-level determinants of innovation

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
139
0
14

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(163 citation statements)
references
References 68 publications
10
139
0
14
Order By: Relevance
“…Precisely, firms from the high-tech industries (e.g., pharmaceutical, chemicals, and electrics) had intensive innovation activities than the firms from low-tech industries (e.g., wearing apparel, manufacture of furniture). Some of the studies revealed positive correlation between innovation and collaboration with customers, competitors, consultant or universities (Kaufmann & Tödtling, 2001;Souitaris, 2002) that supported the evolutionary perspective of the innovation process (Dosi, Freeman, Nelson, Silverberg, & Soete, 1988;Kaufmann & Tödtling, 2001). Certain high-tech firms track results of collaboration by comparing time to market for in-house and partnered product development (Linder, Jarvenpaa, & Davenport, 2003).…”
Section: Theoretical Backgroundmentioning
confidence: 82%
See 2 more Smart Citations
“…Precisely, firms from the high-tech industries (e.g., pharmaceutical, chemicals, and electrics) had intensive innovation activities than the firms from low-tech industries (e.g., wearing apparel, manufacture of furniture). Some of the studies revealed positive correlation between innovation and collaboration with customers, competitors, consultant or universities (Kaufmann & Tödtling, 2001;Souitaris, 2002) that supported the evolutionary perspective of the innovation process (Dosi, Freeman, Nelson, Silverberg, & Soete, 1988;Kaufmann & Tödtling, 2001). Certain high-tech firms track results of collaboration by comparing time to market for in-house and partnered product development (Linder, Jarvenpaa, & Davenport, 2003).…”
Section: Theoretical Backgroundmentioning
confidence: 82%
“…Several factors have been analyzed in the previous literature. Based on extensive review of empirical articles, a conceptual model has been proposed (see Since the late 1960s, organizational theorists have been tried to identify the distinguishing characteristics of innovative organizations at the firm-level (Souitaris, 2002). Firm size has been viewed as an explanatory variable of innovating behavior by many authors (Schumpeter, 1942;Stock, Greis, & Fischer, 2002; Cassiman, 1999;Greve, 2003;Tsai, 2001).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Determinants of innovation are influenced by a number of 'moderating conditions that include (1) firm size, (2) industrial sector the firm belongs to and (3) the environment of the country where the sector and its constituent firm exists (Souitaris, 2002;1999). Becheikh, Landry, and Amara (2006) review empirical innovation studies on manufacturing sectors from 1993-2003 and provide a list of 'internal variables'.…”
Section: Firm-level Determinants Of Lt/lmt Innovationmentioning
confidence: 99%
“…Empirical level has contrasted how various aspects of organizational structure affect innovation, as the existence of work teams (Chiesa et al, 1996;Rothwell, 1992;Souitaris, 2002) A priori, we could think the concepts of flexibility and structure contradict. There is a consensus on the fact that when managing individuals detailing a series of defensive routines or precise standards, organizations are less flexible (Silva & Pontet, 2010).…”
mentioning
confidence: 99%